Migrants, land markets and carbon emissions in Jambi, Indonesia: Land tenure change and the prospect of emission reduction - Galudra, Gamma; van Noordwijk, Meine; Agung, Putra; Suyanto, Suyanto; Pradhan, Ujjwal (Springer, 2014)
Policies designed to reduce land-based carbon emissions require a good understanding of the complex connections between state-sanctioned concessions, forest conversion, informal land markets and migrants. Our case study in the peat forests of the Tanjung Jabung Barat (TanJaBar) regency of Jambi, Indonesia aimed to explore relations between four key stakeholder groups: the state, local communities, migrants, and state-sanctioned concessions. We hypothesized that current land use patterns are shaped by insecurity in formal forest tenure alongside informal land tenure arrangements with migrants. In analyzing the six two-way relationships between the four stakeholder groups, we found that interactions between the stakeholders have changed local norms and practice, causing land conflicts and contested claims that need to be explicitly addressed in efforts to reduce carbon emissions in TanJaBar. Relational concepts of land rights between migrants and local community leaders are informed by social identity, expectations of investment opportunities, insecure customary forest tenure and competing land use policies. Migrants act as intermediaries in shaping the land tenure system and shift the balance of power between local communities, the state, and business concessions. We conclude that effective and equitable implementation of national Reducing Emissions from Deforestation and Forest Degradation+ (REDD+) programs will need to recognize underlying land ownership dynamics, power struggles and strategic positioning among stakeholders across scales. Obtaining free and prior informed consent (FPIC) from all relevant stakeholders is a major challenge given this complexity. Low emission development strategies will require recognition of a reality beyond large-scale concessions and traditional local communities.